2020
DOI: 10.1101/2020.06.10.144212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole Genome Sequencing of SARS-CoV-2: Adapting Illumina Protocols for Quick and Accurate Outbreak Investigation During a Pandemic

Abstract: The COVID-19 pandemic spread very fast around the world. A few days after the first detected case in South Africa, an infection started a large hospital outbreak in Durban, KwaZulu-Natal. Phylogenetic analysis of SARS-CoV-2 genomes can be used to trace the path of transmission within a hospital. It can also identify the source of the outbreak and provide lessons to improve infection prevention and control strategies. In this manuscript, we outline the obstacles we encountered in order to genotype SARS-CoV-2 in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
(16 reference statements)
1
35
0
Order By: Relevance
“…The technique has subsequently been optimized and analysis, albeit in small sample numbers, concluded that it delivers sufficient quality to perform phylogenetic analysis. [18][19][20] It had been used as targeted and random RT-PCR screening with subsequent sequencing of the population in order to study the spread through the community. was early on in the pandemic, it seems more likely that a common source of infection, in-or outside the hospital is the cause.…”
Section: Discussionmentioning
confidence: 99%
“…The technique has subsequently been optimized and analysis, albeit in small sample numbers, concluded that it delivers sufficient quality to perform phylogenetic analysis. [18][19][20] It had been used as targeted and random RT-PCR screening with subsequent sequencing of the population in order to study the spread through the community. was early on in the pandemic, it seems more likely that a common source of infection, in-or outside the hospital is the cause.…”
Section: Discussionmentioning
confidence: 99%
“…We have set up protocols for Illumina, Oxford Nanopore Technologies, PacBio, and Ion Torrent sequencers largely based on open methods developed by the ARTICnetwork. We have also modified Illumina protocols to use an alternative library, which has reduced the hands-on sample processing time by 9 h. 3 As some of the laboratories in the network were prepared when the first cases of COVID-19 were reported in South Africa, we were able to use genomics early in the epidemic to understand the initial spread of the virus, which was characterised by clustered outbreaks. For example, we did a detailed investigation into a nosocomial outbreak in KwaZulu-Natal that began just 4 days after the first reported case in the country.…”
Section: A Genomics Network Established To Respond Rapidly To Publicmentioning
confidence: 99%
“…2,5,6 Short read data are deposited in the Sequence Read Archive every week. Assembled genomes are rapidly shared via the Global Initiative on Sharing All Influenza Data, 3 which is working in collaboration with the NGS-SA to ensure that data generated in South Africa can also be quality controlled and analysed in-country. We believe that open access to data is crucial to facilitate a rapid response to the SARS-CoV-2 pandemic.…”
Section: A Genomics Network Established To Respond Rapidly To Publicmentioning
confidence: 99%
“…Furthermore, DUET web server prognosticated the destabilizing and stabilizing effect of D614G variant of the spike protein and P322L mutation of the nsp12 respectively. As a supplemental study to the obstacles encountered during near-real time SARS-CoV-2 genotyping during pandemic, Pillay et al [45] established 3 lineages (B, B.1 and B.2) from a phylogenetic analysis of 54 near-full-length genome, using Phylogenetic Assignment of Named Global Outbreak LINeages (PANGOLIN) software suite. The 54 genome sequences and 10,959 GISAID reference genomes were aligned using MAFFT v7.313 and a maximum likelihood tree topology constructed in IQ-TREE.…”
Section: Sars-cov-2 Genome Analysis Of African Isolatesmentioning
confidence: 99%